Baby owl's rescue - Curtis, Jennifer Keats (Sylvan Dell Pub., 2009)
What if you found a baby owl in your backyard? Would you know what to do? Where would you go to find help? Join young Maddie and Max as they learn a valuable lesson. Includes "For Creative Minds" section.